Strategi Pengembangan Kawasan Konservasi Hutan Mangrove Desa Bebanga Kecamatan Kalukku Kabupaten Mamuju - Tri Gernamalya Rerung; Rahmawati Rahman; Ilham Yahya (Journal of Urban Planning Studies, 2022)
This study aims to determine the factors that significantly influence the development strategy of mangrove forest conservation areas. This research uses an approach quantitative and qualitative. In this study, the authors use chi-square analysis and inductive data analysis, namely the analysis that begins with data collection (observations, interviews and documentation), then discussion, supporting evidence and ends with conclusions. Furthermore, to develop a strategy for developing a mangrove forest conservation area in Bebanga Village using descriptive analysis methods.